Corrosion-resistant composite material and preparation method and application thereof
Patent Information
- Application Number
- CN202611452813.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-18
- Publication Date
- 2026-10-30
AI Technical Summary
此外,在部分工艺中氨水、尿素或LiOH等物质释放的碱性挥发物也会加剧材料腐蚀
1、在多孔陶瓷基体微孔结构内部形成致密碳填充结构,提高材料致密性;
Smart Images

Figure CN123003303A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of composite material preparation technology, specifically to a corrosion-resistant composite material, its preparation method, and its application. Background Technology
[0002] In the production process of new energy battery materials, cathode materials usually need to undergo solid-state reaction or sintering treatment under high temperature conditions to obtain a stable crystal structure and good electrochemical performance. During this process, the raw materials often release a variety of volatile gases, such as sulfur-containing gases (SO2), phosphorus-containing volatiles (P2O5, phosphoric acid vapor, etc.) and alkaline volatiles (NH3, LiOH, etc.). These gases are highly corrosive at high temperatures, which places high demands on high-temperature container materials.
[0003] Currently, structural materials used in high-temperature sintering or high-temperature reaction environments mainly include mullite ceramic materials and graphite materials. Mullite materials are widely used due to their low cost and mature preparation process. However, their density is relatively insufficient, and micropores and channels usually exist inside the material. In high-temperature corrosive atmospheres, acidic or alkaline volatiles can easily penetrate into the material through these pores, thereby causing corrosion and structural deterioration.
[0004] For example, in the preparation of ternary lithium materials, the precursor often contains trace amounts of sulfate ions, which decompose and release acidic gases under high temperature conditions. These gases can penetrate through the microporous structure of mullite materials and react with the materials, resulting in oxidation, sulfidation and structural deterioration of the material surface.
[0005] During the preparation of lithium iron phosphate materials, phosphoric acid or phosphates release volatile substances such as phosphoric acid vapor, metaphosphoric acid, or P2O5 under high-temperature conditions. These corrosive media can also erode porous ceramic materials. In addition, alkaline volatiles released by substances such as ammonia, urea, or LiOH in some processes can also exacerbate material corrosion.
[0006] Graphite materials have excellent thermal conductivity, high-temperature stability and corrosion resistance, so they have good application effects in high-temperature corrosive environments. However, the raw material cost and processing cost of graphite materials are high, making them less economical in large-scale industrial applications.
[0007] Therefore, existing technologies suffer from the following problems: mullite materials have low cost but insufficient corrosion resistance, while graphite materials have good corrosion resistance but are expensive, making it difficult to balance performance and economy. Therefore, there is an urgent need to develop a composite material that combines high corrosion resistance, good structural stability, and low cost.
[0008] Furthermore, corrosive gas environments such as sulfur-containing gases, acidic vapors, and alkaline volatiles also exist in chemical production and high-temperature gas processing equipment. Porous ceramic materials are also prone to gas permeation corrosion in such environments, while graphite materials face the problem of high cost. Therefore, it is of great significance to develop a composite material that has both high corrosion resistance and low cost. Summary of the Invention
[0009] The purpose of this invention is to provide a corrosion-resistant composite material, its preparation method, and its application, thereby obtaining a composite material that combines high corrosion resistance, good structural stability, and low cost.
[0010] According to the present invention, a corrosion-resistant composite material includes a porous ceramic matrix and a carbon phase, wherein the carbon phase fills the microporous structure of the porous ceramic matrix and the porous ceramic matrix is covered with a continuous carbon protective layer.
[0011] Furthermore, the porous ceramic matrix is one or a mixture of mullite, corundum, and zirconium oxide.
[0012] The present invention also provides a method for preparing the corrosion-resistant composite material as described above, comprising the following steps: S1: Select porous ceramic matrix as the base material; S2: Dry the porous ceramic substrate at 110℃ for no less than 2 hours; S3: After drying the porous ceramic substrate in step S2, place it in a vacuum impregnation device for vacuum treatment, then inject impregnation liquid into the device for impregnation treatment, so that the impregnation liquid enters the pores of the ceramic substrate; S4: Heat-treat the impregnated material by raising the temperature to 140-200℃ and holding it at that temperature for no less than 3 hours. The heating rate is 1-2℃ / 3min, and the pressure is 1.0-1.6MPa. S5: Carburizing treatment is performed by heating the material after heat treatment in step S5 to 350-800℃ and holding it at that temperature for no less than 3 hours. The heating rate is 1-2℃ / min, and the pressure is 1.0-1.6MPa. S6: Cool the material after carburizing in step S5 to room temperature at a rate of 1-2℃ / min.
[0013] Furthermore, in step S3 above, the vacuum degree of the vacuum impregnation equipment is ≥0.096MPa, and the impregnation treatment time is not less than 2 hours.
[0014] Furthermore, after step S3 and before step S4, the pressure of the vacuum impregnation equipment is increased to 1.0-1.6 MPa and maintained for at least 3 hours.
[0015] Furthermore, the impregnation solution is a polymer material system containing a carbon source.
[0016] Furthermore, the main component of the polymer material system is a thermosetting resin.
[0017] Furthermore, the thermosetting resin includes one or more of phenolic resin, furan resin, and epoxy resin.
[0018] This invention also provides the application of the above-mentioned corrosion-resistant composite material in the preparation of high-temperature container products.
[0019] The beneficial effects of this invention are as follows: 1. A dense carbon-filled structure is formed inside the microporous structure of the porous ceramic matrix, improving the material's density; 2. A continuous carbon protective layer is formed on the material surface, effectively preventing the penetration of corrosive gases; 3. It exhibits excellent corrosion resistance in acidic, phosphorus-containing, and alkaline volatile environments; 4. It has a significant cost advantage compared to graphite materials. Attached Figure Description
[0020] Figure 1 The images show a comparison of the SEM morphology of three different material samples under operating condition A.
[0021] Figure 2 This is a comparison of the SEM morphology of three different material samples under operating condition B.
[0022] Figure 3 This is a comparison of the SEM morphology of three different material samples under operating condition C.
[0023] In the figure, reference numeral 1 is the SEM morphology of the corrosion-resistant composite material of the present invention, reference numeral 2 is the SEM morphology of the untreated mullite ceramic material, and reference numeral 3 is the SEM morphology of the commercially available graphite material. Detailed Implementation
[0024] To enable those skilled in the art to better understand the present application, the technical solutions in the embodiments of the present application will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present application, and not all embodiments. Based on the embodiments in the present application, all other embodiments obtained by those of ordinary skill in the art without creative effort should fall within the scope of protection of the present application.
[0025] The present invention provides a corrosion-resistant composite material comprising a porous ceramic matrix and a carbon phase, wherein the carbon phase is filled in the microporous structure of the porous ceramic matrix and the porous ceramic matrix is covered with a continuous carbon protective layer.
[0026] The porous ceramic matrix is one or a mixture of mullite, corundum, and zirconium oxide.
[0027] The present invention also provides a method for preparing the above-mentioned corrosion-resistant composite material, comprising the following steps: S1: Select a porous ceramic matrix as the base material.
[0028] S2: Dry the porous ceramic substrate at 110℃ for no less than 2 hours; S3: After drying the porous ceramic substrate in step S2, place it in a vacuum impregnation device for vacuum treatment, and then inject impregnation liquid into the device for impregnation treatment, so that the impregnation liquid enters the pores of the ceramic substrate.
[0029] S4: Heat-treat the impregnated material by raising the temperature to 140-200℃ and holding it at that temperature for no less than 3 hours. The heating rate is 1-2℃ / 3min, and the pressure is 1.0-1.6MPa. S5: Carburizing treatment is carried out. The material after heat treatment in step S5 is heated to 350-800℃ and held at that temperature for no less than 3 hours. The heating rate is 1-2℃ / min and the pressure is 1.0-1.6MPa.
[0030] S6: Cool the material after carburizing in step S5 to room temperature at a rate of 1-2℃ / min.
[0031] In step S3 above, the vacuum degree of the vacuum impregnation equipment is ≥0.096MPa, and the impregnation treatment time is not less than 2 hours.
[0032] After step S3 and before step S4, the pressure of the vacuum impregnation equipment is increased to 1.0-1.6 MPa and maintained for at least 3 hours.
[0033] The impregnation solution uses a polymer material system containing a carbon source.
[0034] It is worth noting that a nano-reinforcing phase is further added to the impregnation solution. The nano-reinforcing phase is preferably one or more of nano-silicon carbide, nano-boron carbide, or graphene. During the carburizing process, the nano-reinforcing phase can serve as a nucleation point for the formation of carbon structures, thereby forming a stable carbon microstructure network and improving the stability and corrosion resistance of the carbon layer.
[0035] The main component of the polymer material system is thermosetting resin.
[0036] Thermosetting resins include one or more of phenolic resins, furan resins, and epoxy resins.
[0037] This invention also provides the application of the above-mentioned corrosion-resistant composite material in the preparation of high-temperature container products.
[0038] To evaluate the performance of the corrosion-resistant composite material of the present invention, performance tests were also conducted, and comparative tests were performed on the same batch of untreated mullite ceramic material, the corrosion-resistant composite material prepared by the process of the present invention, and commercially available graphite material.
[0039] The test results were obtained by observing the surface morphology of the samples using a scanning electron microscope, as shown in the attached figures. Figure 1 Appendix Figure 2 and attached Figure 3 As shown in the figures, reference numeral 1 is the SEM morphology image of the corrosion-resistant composite material of the present invention, reference numeral 2 is the SEM morphology image of the untreated mullite ceramic material, and reference numeral 3 is the SEM morphology image of the commercially available graphite material.
[0040] Before testing, all samples were dried at 110°C for 2 hours, cooled, and weighed to obtain initial mass, in order to eliminate variable interference.
[0041] The above three samples were subjected to simulated tests under three different working conditions, where: Condition A simulates the decomposition of sulfate to produce acidic gas in the ternary lithium process. The environment contains SO2 gas, the temperature is set to 800°C, inert gas (N2) is added, and the temperature is maintained for 72 hours. Operating condition B simulates volatile phosphoric acid, with an environment containing phosphoric acid gas, and the temperature is set at 600°C for 72 hours. Operating condition C simulates alkaline volatiles, with an environment containing ammonia-based alkaline gas, and the temperature is set at 600°C for 72 hours.
[0042] Testing and Characterization Methods Mass loss: The mass of each sample before and after the experiment was measured using a high-precision electronic balance (±0.01mg) to obtain the cumulative mass loss. Corrosion rate: The average corrosion rate was estimated using the weight loss method, based on the mass loss over 72 hours. Surface morphology inspection: The samples were observed by scanning electron microscopy before and after the experiment to check the surface condition.
[0043] All samples were observed under the same scanning electron microscope conditions, with a magnification of 2000x and a scale bar of 10 μm.
[0044] Experimental observation Condition A: No obvious corrosion or slag was observed in the graphite material under 72h conditions, with an average corrosion rate of 0.03mm / year; the pure mullite ceramic matrix material showed obvious corrosion and slag, with visible spalling products on the surface, and an average corrosion rate of 0.73mm / year; the composite material showed no obvious corrosion or slag under the same conditions, with an average corrosion rate of 0.03mm / year.
[0045] like Figure 1As shown, the surface morphology of the composite material sample indicated by label 1 is relatively smooth and dense, with no obvious corrosion or surface peeling. The surface morphology of the untreated mullite ceramic material indicated by label 2 is obviously rough, with obvious unevenness and local corrosion characteristics, accompanied by surface material peeling. The surface morphology of the commercially available graphite material indicated by label 3 is relatively smooth and dense, with no obvious corrosion or surface peeling.
[0046] Condition B: No obvious corrosion or slag was observed in the graphite material under 72h conditions, with an average corrosion rate of 0.02mm / year; the pure mullite ceramic matrix material showed obvious corrosion and slag, with visible spalling products on the surface, and an average corrosion rate of 0.63mm / year; the composite material showed no obvious corrosion or slag under the same conditions, with an average corrosion rate of 0.02mm / year.
[0047] like Figure 2 As shown, the surface morphology of the composite material sample indicated by label 1 is relatively uniform and dense, with no obvious corrosion or surface peeling. The surface morphology of the untreated mullite ceramic material indicated by label 2 is obviously rough, with obvious unevenness, pores and local corrosion characteristics, accompanied by surface material peeling. The surface morphology of the commercially available graphite material indicated by label 3 is relatively uniform and dense, with no obvious corrosion or surface peeling.
[0048] Condition C: No obvious corrosion or slagging was observed in the graphite material under 72h conditions, with an average corrosion rate of 0.03mm / year; the pure mullite ceramic material matrix showed some slagging, with an average corrosion rate of 0.36mm / year; the composite material showed no obvious corrosion or slagging under the same conditions, with an average corrosion rate of 0.03mm / year.
[0049] like Figure 3 As shown, the surface morphology of the composite material sample with label 1 is relatively uniform, and no obvious corrosion or surface peeling is observed; the surface morphology of the untreated mullite ceramic material with label 2 is obviously rough, showing obvious undulations and corrosion characteristics such as irregular holes and grooves, and there are obvious surface damage and peeling phenomena in some areas; the surface of the commercially available graphite material with label 3 is generally uniform, and no obvious corrosion or surface peeling is observed.
[0050] Experimental results show that, under the above three typical simulated working conditions, the corrosion-resistant composite material of the present invention exhibits corrosion resistance performance that is basically consistent with that of graphite materials; however, compared with traditional pure ceramic materials, the composite material significantly improves corrosion resistance in acidic, phosphorus-containing, and alkaline volatile environments, and no obvious slagging or surface deterioration is observed.
[0051] As can be seen from the above, the microporous structure of the carbon phase-filled porous ceramic matrix, combined with the external continuous carbon protective layer, effectively blocks the penetration and erosion of acidic, alkaline, and phosphorus-containing high-temperature corrosive media into the ceramic interior. The preparation process of vacuum impregnation, pressure curing, and temperature-controlled carburizing can enable the impregnation liquid to fully enter the ceramic pores and transform into a continuous carbon phase, so that the ceramic matrix is transformed from an easily corroded porous structure into a dense and corrosion-resistant composite structure.
[0052] By using ceramic matrices such as mullite, corundum, and zirconium oxide, and combining them with phenolic / furan / epoxy thermosetting resin carbon sources, stable carbon phase composites are achieved while ensuring high temperature resistance.
[0053] As can be seen from the above, the nano-reinforcing phase, as the nucleation site of the carbon structure, can provide attachment and growth sites for the carbon phase during the carburizing process. This allows the carbon formed by resin decomposition to be distributed more evenly and continuously in the ceramic pores and surface. At the same time, it forms a stable carbon microstructure network, allowing the carbon filling the ceramic micropores and the carbon protective layer on the surface to form a dense, strong, and unbreakable micro-network structure. This prevents the carbon layer from cracking and falling off, and improves the stability of the carbon layer. This makes the carbon phase more resistant to oxidation and corrosion under high temperature, acidic / alkaline / phosphorus-containing corrosive atmospheres, and the structure more durable. Combined with the internal carbon filling and the external carbon protective layer, it further blocks the penetration of corrosive gases, making the material more stable in high-temperature corrosive environments.
[0054] In summary, this invention maintains corrosion resistance close to that of graphite materials while offering significant cost advantages, providing a material solution that combines high corrosion resistance with low cost for sintering equipment for new energy battery materials, high-temperature reaction equipment, and other high-temperature corrosive environments.
[0055] The above description is only a preferred embodiment of this application. It should be noted that for those skilled in the art, several improvements and modifications can be made without departing from the principle of this application, and these improvements and modifications should also be considered within the scope of protection of this application.
Claims
1. A corrosion-resistant composite material, characterized in that, It includes a porous ceramic matrix and a carbon phase, wherein the carbon phase fills the microporous structure of the porous ceramic matrix and the porous ceramic matrix is covered with a continuous carbon protective layer.
2. The corrosion-resistant composite material according to claim 1, characterized in that, The porous ceramic matrix is one or a mixture of mullite, corundum, and zirconium oxide.
3. A method for preparing a corrosion-resistant composite material as described in any one of claims 1-2, characterized in that, Including the following steps: S1: Select porous ceramic matrix as the base material; S2: Dry the porous ceramic substrate at 110℃ for no less than 2 hours; S3: After drying the porous ceramic substrate in step S2, place it in a vacuum impregnation device for vacuum treatment, then inject impregnation liquid into the device for impregnation treatment, so that the impregnation liquid enters the pores of the ceramic substrate; S4: Heat-treat the impregnated material by raising the temperature to 140-200℃ and holding it at that temperature for no less than 3 hours. The heating rate is 1-2℃ / 3min, and the pressure is 1.0-1.6MPa. S5: Carburizing treatment is performed by heating the material after heat treatment in step S5 to 350-800℃ and holding it at that temperature for no less than 3 hours. The heating rate is 1-2℃ / min, and the pressure is 1.0-1.6MPa. S6: Cool the material after carburizing in step S5 to room temperature at a rate of 1-2℃ / min.
4. The method for preparing the corrosion-resistant composite material according to claim 3, characterized in that, In step S3 above, the vacuum degree of the vacuum impregnation equipment is ≥0.096MPa, and the impregnation treatment time is not less than 2 hours.
5. The method for preparing the corrosion-resistant composite material according to claim 3, characterized in that, After step S3 and before step S4, the pressure of the vacuum impregnation equipment is increased to 1.0-1.6 MPa and maintained for at least 3 hours.
6. The method for preparing the corrosion-resistant composite material according to claim 3, characterized in that, The impregnation solution uses a polymer material system containing a carbon source.
7. The method for preparing the corrosion-resistant composite material according to claim 6, characterized in that, The main component of the polymer material system is a thermosetting resin.
8. The method for preparing the corrosion-resistant composite material according to claim 7, characterized in that, The thermosetting resin includes one or more of phenolic resin, furan resin, and epoxy resin.
9. The application of the corrosion-resistant composite material according to any one of claims 1-2 in the preparation of high-temperature container products.